Governmental policies to confront unemployment and achieve human development in Algeria in the Economic recovery programs during the period 2003-2013: Social-economic study of unemployment - Ali bakchiche (Dirassat Journal Economic Issue, 2016)
Given the Algerian economy in recent years, a steady drop in the unemployment rate, due to the economic policy of the court pursued by Algeria during the period from 1999 to the present, through the adoption of economic reforms and development programs online, in accordance with the requirements of the global economy, which, in contrast to positively on the individual and society in different areas of life. With the availability of the political will announced is clearly with the macroeconomic framework is stable and adapted and the recording of the return of growth outside the hydrocarbon sector and a large foreign exchange reserve to control the inflation and investment programs public and private and the return of peace and stability, of all these things statement stimuli to eliminate the scourge of the exhausted Algeria for several years represented in the unemployment crisis, so deliberately State to develop a special program of polyphase of human development aims to rationalize spending and diversify drivers through regional and local development agencies, in order to increase the number of youth funds and support the creation of small and medium-sized enterprises, also held Algeria to facilitate the funding process and ease the pressure on students to work r with the aim of granting possibilities for the two professional groups, and estimated for the period 2009-2013 to provide 452,585 jobs on average per year. This means that Algeria was a long way to eliminate unemployment is the greatest challenge of achieving global development, if we know that unemployment is the main indicator to measure the rate of human development